EFFECTS OF RED YAM FLOUR (Ipomoea batatas L.) ON THE GROWTH, SURVIVAL RATE AND SKIN COLOR OF GOLDFISH (Carassius auratus) - Dedi Fazriansyah Putra; Lia Armaya; Sayyid Afdhal El Rahimi; Norhayati Othman (BIOTROPIA, 2019)
The best quality goldfish requires a good environment and a highly nutritious feed. Thus, this study evaluated the effects of commercial diets supplemented with 0%, 3%, 6%, 9% and 12% red yam flour (Ipomoea batatas L.) on the growth rate, survival rate and skin color of the goldfish Carrasius auratus. A completely randomized experimental design with five treatments and three replicates was used. Seventy-five goldfishes with an average initial length of 4.4 cm were fed the supplemented commercial diets for twenty-eight days inside fifteen experimental tanks. The results showed that the 9% dietary treatment significantly affected the skin color of the goldfishes but not their growth and survival rates (P > 0.05). Hence, the administration of 9% concentrated red yam flour was a suitable dietary supplement to improve skin pigmentation, an important characteristic of aquarium fishes.